Rapt [compact disc, unabridged] : attention and the focused life - Gallagher, Winifred (Brilliance Audio, 2009)
Behavioral science writer Winifred Gallagher makes the argument that the quality of your life largely depends on what you choose to pay attention to and how you choose to do it. Gallagher grapples with provocative questions--Can we train our focus? What's different about the way creative people pay attention? Why do we often zero in on the wrong factors when making big decisions?--driving us to reconsider what we think we know about attention.